1990
DOI: 10.1111/j.1471-4159.1990.tb01231.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Asymmetric and Globular Acetylcholinesterase Species with Glycosaminoglycans

Abstract: Chicken muscle and retina, and rat muscle asymmetric acetylcholinesterase (AChE) species were bound to immobilized heparin at 0.4 M NaCl. Binding efficiency was between 50 and 80% for crude fraction I A-forms (AI; muscle), and nearly 100% for fraction II A-forms (AII; muscle and retina). Antibody-affinity-purified AI-forms (chicken) were, however, quantitatively bound to heparin-agarose gels, whereas diisopropylfluorophosphate-inactivated high-salt extracts partially prevented the binding of both AI and AII AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…We have checked three different heparinases taking into account the structural heterogeneity of the heparin/heparan sulfate family of GAGS: it is, for instance, a proven fact that heparan sulfates do often contain long heparin-like stretches [ 121. Besides, in our hands, heparin shows consistently more affinity for tailed AChE forms than heparan sulfate itself [8,9]. Actually, these enzymes show mixed specificities: 'heparinase' (heparinases I and II) acts equally well upon heparin and heparitin sulfaies C and D, wherecs heparitinase I (heparinase III) degra Ies only heparitin sulfates A and B [13].…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…We have checked three different heparinases taking into account the structural heterogeneity of the heparin/heparan sulfate family of GAGS: it is, for instance, a proven fact that heparan sulfates do often contain long heparin-like stretches [ 121. Besides, in our hands, heparin shows consistently more affinity for tailed AChE forms than heparan sulfate itself [8,9]. Actually, these enzymes show mixed specificities: 'heparinase' (heparinases I and II) acts equally well upon heparin and heparitin sulfaies C and D, wherecs heparitinase I (heparinase III) degra Ies only heparitin sulfates A and B [13].…”
Section: Resultsmentioning
confidence: 85%
“…To explore, within the latter hypothesis, the possibility of a joint involvement of both heparan and chondroitin sulfates in the attachment of extracellular muscle AChE we also measured the release of A-forms by a mixture of all heparinases Ten-day chick muscle samples, preextracted with TT buffer, were incubated with 5 U/ml of chondroitinase, as described in section 2, along with control samples (background -Bckg -control, containing no enzyme, and maximal release control -valid only for A-forms -, containing high salt and EDTA). The digested samples were usually freed of the coarse particulate material by filtration, and then layered on top of a S-2O"Io sucrose gradient, made up in TTSE buffer, together with sedimentation markers [8]. These gradients were run, fractionated and assayed for ACM2 (nmol ['"CJacetate released per min and fraction) and marker enzyme activities as described IB].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is based on the following findings : (1) The bulk of the enzyme is extracted at low ionic strength, in the presence of detergent ; (2) sedimentation on sucrose gradients is not affected by collagenase ; and (3) the close migration of the 6.5 S and 8 S species on gel filtration ( Figure 5) argues against the 8 S species being an A % form, rather than a G form. Although this assignment is unusual, interaction of G forms of both AChE and butyrylcholinesterase with heparin has been reported [22,23].…”
Section: Discussionmentioning
confidence: 87%
“…The G forms of AChE lack the collagen tail, and are usually considered to lack the capacity to interact with heparin. However, Ramirez et al [22] showed that the G % form from chick muscle binds to heparin with low affinity. Furthermore, Sine et al [23] reported an interaction with heparin by an amphiphilic G # form of butyrylcholinesterase extracted from mucosal cells of rat intestine.…”
Section: Introductionmentioning
confidence: 99%